2000
DOI: 10.1080/713696677
|View full text |Cite
|
Sign up to set email alerts
|

Socio-emotional Orientation as a Mediating Variable in the Teaching‐Learning Interaction: Implications for instructional design

Abstract: In this paper we argue that many of the design decisions of modern pedagogical solutions are made unconsciously without articulated view of the issues being addressed by the complex relationship of student's social, emotional and motivational interpretations in learning. We present a theoretical framework for analysing them and discuss of the two empirical experiments, where individual students' social and motivational interpretations were analyzed in a cognitive apprenticeship based technologically rich learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 16 publications
(17 reference statements)
0
23
0
1
Order By: Relevance
“…Epistemic solutions, which focus on the task, led to better learning and more positive perceived relationships, whereas relational solutions, which focus on the relative competence of participants, were associated with worse learning and more negative relationships than controls. Jarvelä, Lehtinen, and Salonen (2000) identify individual differences in emotional orientation to tasks, especially at points of challenge, which might underlie the tendency to seek one or other type of solution to group conflicts. The implication is that whilst positive relationships are not a pre-condition, social growth from collaborative learning is more likely if this activity is preceded by a period of preparation, during which explicit ground rules for dealing with conflicts in epistemic fashion are established.…”
Section: Possible Relationships Between Cognitive and Social Gainsmentioning
confidence: 99%
“…Epistemic solutions, which focus on the task, led to better learning and more positive perceived relationships, whereas relational solutions, which focus on the relative competence of participants, were associated with worse learning and more negative relationships than controls. Jarvelä, Lehtinen, and Salonen (2000) identify individual differences in emotional orientation to tasks, especially at points of challenge, which might underlie the tendency to seek one or other type of solution to group conflicts. The implication is that whilst positive relationships are not a pre-condition, social growth from collaborative learning is more likely if this activity is preceded by a period of preparation, during which explicit ground rules for dealing with conflicts in epistemic fashion are established.…”
Section: Possible Relationships Between Cognitive and Social Gainsmentioning
confidence: 99%
“…Group work can, for example, create positive emotions and support group members' motivation (Jones and Isroff 2005;Järvenoja and Järvelä 2013). However, group situations can also arouse negative emotions if group members' personal demands or goals conflict and thus may lead to demotivation or even withdrawal (Järvelä et al 2000;Järvenoja and Järvelä 2013). Pekrun et al (2002) have suggested that students experience positive emotions as often as negative ones.…”
Section: Introductionmentioning
confidence: 98%
“…In Hanna's case Knowledge Forum provided a socially safe forum for computer note exchanges with other students which she preferred over face to face interaction. One more perspective for students' engagement may deal with individual student socioemotional needs (Järvelä et al 2000). Computer supported inquiry can open up more "space" for them.…”
Section: Discussionmentioning
confidence: 99%